E-Reputation Management as a Mechanism for Attracting and Retaining Talent - Sofiane Mansouri; Fairouz Chine (Journal of Science and Knowledge Horizons, 2025)
The reputation of an organisation has shifted from traditional notions to electronic concepts linked to the advancement of information and communication technology. These transformations have introduced numerous concepts that organisations must address and adapt to by maintaining vigilance and responsiveness, utilising them to create added value. This paper aimed to review the significance of electronic reputation management in attracting talents and competencies from the labour market, with a narrative approach based on multiple relevant sources. The paper concluded that effective management of an organisation’s electronic reputation markedly enhances its ability to attract talented, experienced, and competent individuals. However, the research also cautions against relying exclusively on digital platforms for managing organisational reputation.